Tuberculous and non‐tuberculous cervical lymphadenopathy incidence and distribution in Somalia from 2016 to 2020: A review of 241 cases. Issue 4 (5th May 2022) - Tahtabasi, Mehmet; Sahiner, Fatih
Abstract: Objective: To determine the incidence of tuberculous lymphadenitis (TBL) and other pathologies in cervical lymphadenopathies in Somalia and accompanying radiological findings. Methods: In this hospital‐based retrospective study, the demographic characteristics, pathology results and radiological findings of 263 patients who underwent ultrasound (US)‐guided cervical lymph node biopsy between January 2016 and February 2020 were analyzed. Results: Of 241 patients 118 men and 123 women (mean age 27.9 ± 18.1 years) included in the study, 46.1% ( n = 111) were diagnosed as necrotizing granulomatous lymphadenitis (caseified, consistent with TBL) and 21.6% ( n = 12, atypical lymphoid cells and n = 40, metastases) as malignancy. The most common type of metastasis was squamous cell cancer ( n = 31), and the primary source of most of them was esophageal cancer (16/31, 51.6%). The age of patients with TBL was significantly lower than that of non‐TBL (21.9 ± 14.6 vs . 41.9 ± 24.6, P = 0.003) and the incidence of TBL in pediatric patients was statistically higher (58.0% vs . 21.5%, P = 0.019). The rate of patients with TBL being localized at level 4 and level 5 was significantly more than non‐TBL patients (18.0% vs . 10.0% and 23.4% vs . 10.8%, respectively, P = 0.01). Half of patients with TBL who have chest radiography had pathological findings; consolidation and bronchopneumonia were present in 52.6% of them. There were 2 patients with paravertebral abscess and one patient with gastrointestinal tuberculosis. Conclusion: In Somalia, in the presence of cervical lymphadenopathy, after diagnosis by using US‐guided biopsy; primarily considering of TBL and malignancy, thoracic involvement should be investigated, and esophageal carcinoma must be excluded in terms of metastatic lymph node.